Effect of nitrogen on the seasonal course of growth and maintenance respiration in stems of Norway spruce trees - Stockfors, Jan; Linder, Sune (Tree Physiology, 1998)
To determine effects of stem nitrogen concentration ([N]) on the seasonal course of respiration, rates of stem respiration of ten control and ten irrigated–fertilized (IL), 30-year-old Norway spruce trees ( Picea abies (L.) Karst.), growing in northern Sweden, were measured on seven occasions from June 1993 to April 1994. To explore sources of seasonal variation and mechanisms of fertilization effects on respiration, we separated total respiration into growth and maintenance respiration for both xylem and phloem bark. Stem respiration increased in response to the IL treatment and was positively correlated with growth rate, volume of living cells and stem nitrogen content. However, no significant effect of IL treatment or [N] in the living cells was found for respiration per unit volume of live cells. Total stem respiration during the growing season (June to September) was estimated to be 16.7 and 29.7 mol CO 2 m−2 for control and IL-treated trees, respectively. Respiration during the growing season accounted for approximately 64% of total annual respiration. Depending on the method, estimated growth respiration varied between 40 and 60% of total respiration during the growing season. Between 75 and 80% of the live cell volume in the stems was in the phloem, and phloem maintenance accounted for about 70% of maintenance respiration. Because most of the living cells were found in the phloem, and the living xylem cells were concentrated in the outer growth rings, we concluded that the best base for expressing rates of stem growth and maintenance respiration in young Norway spruce trees is stem surface area.